(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The social fabric of a population is of utmost importance to know the scenario of HIV/AIDS in that population. This paper highlights vulnerability of women towards the disease based on their socio-economic characteristics. It is a cross-sectional study among the Jaintia tribal women of Meghalaya belonging to the reproductive and vulnerable age group (15-35years). The methods used for data collection are structured interview schedules, participant observation, focussed group discussions and in-depth interviews. The findings revealed that majority of the women are poor and uneducated and as a result, this has an impact on their role and ability to protect them from contracting the disease.